2008
DOI: 10.1111/j.1750-3841.2008.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐Lowering and LDL‐Oxidation Inhibitory Effects of Aqueous Extract of Freshwater Clam (Corbicula fluminea)—Using Tilapia As an Animal Model

Abstract: A previous study has demonstrated that tilapia able to exhibit hyperlipidemia and hypercholesterolemia is a good model for the evaluation of beneficial effects of nutraceuticals. In this study, tilapia were used to evaluate the in vitro and in vivo effects of a hot water extract (FC-HW) of freshwater clam (Corbicula fluminea). FC-HW prolonged the lag phase of Cu(2+)-induced human and tilapia LDL oxidation. The prolongation of the lag phase was concentration-dependent in human (r(2)= 0.94) and tilapia LDL (r(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Clams are not only a source of protein, but also have hypocholesterolemic activities, which have been confirmed in freshwater clam (Corbicula fluminea) extract (Chen, Lin, Shiao, & Pan, 2008;Chijimatsu, Tatsuguchi, Abe, Oda, & Mochizuki, 2008), seaweed polysaccharides, and a seaweed mixture including brown and red seaweeds (Suzuki, Ohsugi, Yoshie, Shirai, & Hirano, 1996;Wang, Onnagawa, Yoshie, & Suzuki, 2001). The hypocholesterolemic activity of clam hydrolysates and the dietary fibres of seaweeds have contributed to the suppression of both cholesterol adsorption and cholesterol micellar solubility, in addition to inhibition of ileal re-adsorption of bile acids (Gallaher, Hassel, & Lee, 1993;Zhong, Liu, Ma, & Shoemaker, 2007).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Clams are not only a source of protein, but also have hypocholesterolemic activities, which have been confirmed in freshwater clam (Corbicula fluminea) extract (Chen, Lin, Shiao, & Pan, 2008;Chijimatsu, Tatsuguchi, Abe, Oda, & Mochizuki, 2008), seaweed polysaccharides, and a seaweed mixture including brown and red seaweeds (Suzuki, Ohsugi, Yoshie, Shirai, & Hirano, 1996;Wang, Onnagawa, Yoshie, & Suzuki, 2001). The hypocholesterolemic activity of clam hydrolysates and the dietary fibres of seaweeds have contributed to the suppression of both cholesterol adsorption and cholesterol micellar solubility, in addition to inhibition of ileal re-adsorption of bile acids (Gallaher, Hassel, & Lee, 1993;Zhong, Liu, Ma, & Shoemaker, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…The hydrolysate shows inhibitory effects on angiotensin I-converting enzyme (ACE) with an IC 50 value of 0.043 mg/ml (Tsai, Lin, Chen, & Pan, 2006). Additional studies showed that the hot water extract of freshwater clam meat has hypocholesterolemic effects on rats (Chijimatsu et al, 2008) and in tilapia, a surrogate animal model (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…35.1). The LDL oxidation rate in the propagation phase and the maximal oxidative state are reduced by the dietary intake of the clam extract [30].…”
Section: Antioxidative Activitymentioning
confidence: 99%
“…Total cholesterol, triacylglycerols (TAG), and LDL cholesterol were reduced in the plasma of tilapia fed feed fortified with dried hot-water extract of freshwater clam (Table 35.1) [30], which is effective in cholesterol and lipid regulation.…”
Section: Hypolipidemia and Hypocholesterolemia Activitymentioning
confidence: 99%
“…The freshwater clam, Corbicula fluminea, has been successfully cultured in Taiwan and the hot-water extraction of clams has been commercialized for health products [1], domestic consumption, and export to other Asian countries. Small portions of the clamshell are used as food additive and the large remainder is considered commercial waste.…”
Section: Introductionmentioning
confidence: 99%